Esophageal Stent Insertion for Postesophagectomy Anastomosis Site Leakage - Sang Yoon Kim; Chang Hyun Kang; In Kyu Park; Young Tae Kim (Clinical and Experimental Otorhinolaryngology, 2016)
In Ivor Lewis operation, anastomosis site leakage is a critical complication. Interventional approach utilizing covered metal stent has been introduced for the management of this complication. This patient was diagnosed as esophageal cancer and underwent robot-assisted Ivor Lewis operation. Due to symptoms suggesting anastomosis site leakage, video-assisted thoracoscopic surgery exploration was performed without identification of gross leakage site. On esophagogastroduodenoscopy, anastomosis site leakage was detected and esophageal stent was placed. Four weeks later, the stent was removed, and the patient could intake all his diet orally without discomfort. Esophageal stent insertion can be an option to manage postesophagectomy leakage problem.